Geography and covid-19: reflections from the evolution of the pandemic in Uberlândia, Brazil - Souza, Josimar dos Reis de; Souza, Tatiana Silva; Soares, Beatriz Ribeiro (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
From the complex sanitary moment faced by Brazil, related to COVID-19, in particular due to the collapse of the health system that has occurred in medium-sized cities, this article aimed to analyze the evolution of the COVID-19 pandemic in Uberlândia, according to reflections from geographic science, in order to help to understand the facts that led to the current scenario of the disease in the city. To achieve the objective, we carried out a theoretical discussion about how Geography faces recent events, especially in relation to the role of the Globalization process, both in the dissemination of information about the emergence of COVID-19 and other events, as well as in the rapid spread of the virus around the world. Based on these reflections, we analyzed the evolution of the pandemic, using data provided by the Municipality of Uberlândia and the Ministry of Health, with a cut-off date of March 18, 2021, in order to understand the chronological path of the facts. The choice for this cut-off date for data clipping is justified by our intention to analyze the first year of virus identification in the municipality. The results showed the negative evolution of the pandemic in the city, mainly over the months of February and March 2021, with 100% of the ICU beds occupied, which demonstrates the complexity and the long way to go to overcome this health crisis.